Greenhouse gas formation in ice wedges at Cyuie, central Yakutia. (15th January 2019) - Kim, Kyungmin; Yang, Ji‐Woong; Yoon, Hyunsuk; Byun, Eunji; Fedorov, Alexander; Ryu, Yeongjun; Ahn, Jinho
Abstract: Greenhouse gases (GHGs) trapped in ice wedges may provide useful information on biogeochemical environments in ground ice. Previous studies have reported highly elevated CO2 and CH4 mixing ratios in ice wedges. However, N2 O mixing ratios in ice wedges remain unknown. Here, we present CO2, CH4 and N2 O mixing ratios in bubbles and plausible mechanisms of GHG formation for two lakeside ice wedges at Cyuie village near Yakutsk. The CO2 gas age corresponds to the Last Glacial Maximum (18–19 ka). The δ(N2 /Ar) values and bubble shapes indicate that the ice wedges formed by dry snow compaction rather than snowmelt water refreezing, while the δ 18 O and δD values of the ice indicate changes in the source area location and/or the climate during the Last Glacial Maximum. Using a dry extraction method, we obtained gas mixing ratios of 7–13% CO2, 5–130 ppm CH4 and 100–5000 ppb N2 O. The δ(O2 /Ar) values imply that most of the O2 was consumed by biological respiration. The CH4 is negatively correlated with N2 O and CO2 . The N2 O might have inhibited CH4 production.